Atuação dos enfermeiros da estratégia de saúde da família frente à violência intrafamiliar contra a criança - Bezerra, Kelianny Pinheiro (2009)
The family violence against children became visible, in the context of public health, due to the damage and injuries generated in the lives of children and to the growing need of investment in physical and human resources to fill this demand. In this context, it is believed that intervention could prevent such events and are configured as primary strategies to prevent the corollaries generated by the violence. In this perspective, this study aims to analyze the performance of nurses dealing with the Strategy of Family Health viewing to identify actions based on the paradigm of health distribution. This is a descriptive, exploratory and qualitative research. The data were analyzed based on the content analysis about the method proposed by Bardin. The study was conducted in Mossoró-RN and the participants were 14 nurses working for the Family Health Strategy in Health Units of this town. The instrument for data collection was a semi-structured questionnaire, with questions answered by the participants themselves. It was evident to the study that the nurses believe that health education are the main tool for dealing with domestic violence against children, being developed, however, in its positivist and vertical way. The actions used to develop health performed by the team on their daily lives are limited to educational activities and are carried exactly when cases of family violence against children are notified. Barriers to the practice emerged from fear of reprisals from the agressor, overwork, lack of management support and difficulty for the realization of interdisciplinary, intersectorality and comprehensive care.